IMPLEMENTASI KEBIJAKAN PENGEMBANGAN EKONOMI KREATIF MELALUI PROGRAM SUKABUMI CREATIVE HUB - Denia Yurisa; Aufarul Marom; Herbasuki Nurcahyanto (Journal of Public Policy and Management Review, 2023)
Labor problems in Sukabumi City include a very large number of workforce, relatively low quality workforce and job opportunities that are not comparable to job seekers. The labor force participation rate from 2019 to 2021 has not reached the target, namely the 2021 target of 67% but in reality it only reached 56.86%. Medium or micro creative industries have the potential to apply labor because employment in the creative industry/economic sector can be increased. This effort was carried out by establishing the Sukabumi Creative Hub Program. This study aims to analyze the implementation of creative economic development policies through the Sukabumi Creative Hub Program and to analyze the inhibiting factors as well as the driving factors in its implementation. The research method used is descriptive qualitative with data collection techniques by interviews, observation, and documentation. The implementation of the Sukabumi Creative Hub program is seen from the Extent Change of Envision, namely the target to be achieved, the Type of Benefits, namely the positive impact produced and the Resources Committed or resources. Meanwhile, in looking at the inhibiting and driving factors, using previous research from Alvin Rizalsan and Vishnu Juwono which consists of clarity of vision and mission, planning, clear division of tasks, standardization and supervision. The implementation of the Sukabumi Creative Hub Program has been going well although there are still obstacles. In the implementation of the Sukabumi Creative Hub program, there is a driving factor, namely the budget that is prioritized and freed to seek independent budgets. While the inhibiting factors are the inadequate facilities and infrastructure as well as their maintenance, the policies of the central government and local governments are not yet connected or there is no local regulation or regulation that regulates creative economy development in Sukabumi City, and there is no honorarium or incentives for the Sukabumi Creative Hub committee.